Persepsi Generasi Z Batak Toba dalam Memaknai Tradisi Pemberian Manuk Naniatur di Desa Pegagan Julu VI Kecamatan Sumbul Kabupaten Dairi - Jesika Bakara; Muhammad Iqbal (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the perceptions of Generation Z members of the Toba Batak ethnic group in Pegagan Julu VI Village, Sumbul District, Dairi Regency, regarding the symbolic meaning of the tradition of giving manuk naniatur (a traditional gift) and the shifting meaning or function of this tradition according to Generation Z. The method used was qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation. The results indicate that the tradition of giving manuk naniatur is still routinely practiced and has become a local custom. Most Generation Z members value this tradition as an important part of their cultural identity and ancestral heritage, although not all understand its symbols deeply. This tradition is seen as an expression of love and gratitude to God, as well as a sign of blessing, hope, encouragement, and strength for children or families who have migrated. However, there has been a shift in meaning in Generation Z's perspective, from the tradition previously seen as a symbol of respect and spiritual bonding to now being seen more as a cultural identity and shared values ​​that must be maintained. This study illustrates the dynamics of traditional cultural preservation and adaptation to the changing times among the younger generation of the Toba Batak ethnic group.